Innovative approach for increasing physical activity among breast cancer survivors: protocol for Project MOVE, a quasi-experimental study. Issue 8 (16th August 2016) - Caperchione, Cristina M; Sabiston, Catherine M; Clark, Marianne I; Bottorff, Joan L; Toxopeus, Renee; Campbell, Kristin L; Eves, Neil D; Ellard, Susan L; Gotay, Carolyn
Abstract : Introduction: Physical activity is a cost-effective and non-pharmaceutical strategy that can help mitigate the physical and psychological health challenges associated with breast cancer survivorship. However, up to 70% of women breast cancer survivors are not meeting minimum recommended physical activity guidelines. Project MOVE is an innovative approach to increase physical activity among breast cancer survivors through the use of Action Grants, a combination of microgrants (small amounts of money awarded to groups of individuals to support a physical activity initiative) and financial incentives. The purpose of this paper is to describe the rationale and protocol of Project MOVE. Method and analysis: A quasi-experimental pre–post design will be used. Twelve groups of 8–12 adult women who are breast cancer survivors (N=132) were recruited for the study via face-to-face meetings with breast cancer-related stakeholders, local print and radio media, social media, and pamphlets and posters at community organisations and medical clinics. Each group submitted a microgrant application outlining their proposed physical activity initiative. Successful applicants were determined by a grant review panel and informed of a financial incentive on meeting their physical activity goals. An evaluation of feasibility will be guided by the reach, effectiveness, adoption, implementation, maintenance (RE-AIM) framework and assessed through focus groups, interviews and project-related reports. Physical activity will be assessed through accelerometry and by self-report. Quality of life, motivation to exercise and social connection will also be assessed through self-report. Assessments will occur at baseline, 6 months and 1 year. Ethics and dissemination: Ethical approval was obtained from the University of British Columbia's Behavioural Research Ethics Board (#H14-02502) and has been funded by the Canadian Cancer Society Research Institute (project number #702913). Study findings will be disseminated widely through peer-reviewed publications, academic conferences, local community-based presentations, as well as partner organisations, including the Canadian Cancer Society.